Integrin CD11b provides a new marker of pre-germinal center IgA+ B cells in murine Peyer's patches. (31st December 2021) - Gao, Peng; Adachi, Takahiro; Okai, Shinsaku; Morita, Naoki; Kitamura, Daisuke; Shinkura, Reiko
Abstract: Activated B cells can enter germinal centers (GCs) for affinity maturation to produce high-affinity antibodies. However, which activated B cells will enter GCs remains unknown. Here, we found a small population of CD11b + IgA + B cells located outside of GCs in murine Peyer's patches (PPs). After injection of the CD11b + IgA + PP B cells into a PP of a recipient mouse, they entered GCs forty hours later. They expressed GC surface markers and pre-GC B cell genes, suggesting that CD11b provides a novel surface marker of pre-GC IgA + B cells in murine PPs. Furthermore, independently of dendritic cell activation, CD11b expression on B cells can be induced by bacterial antigens, such as pam3CSK4 and heat-killed Escherichia coli in vitro. In addition, mice orally administered with pam3CSK4 or heat-killed E. coli increased the number of PP GC B cells within two days, and enhanced the mucosal antigen-specific IgA response. Our results demonstrate that the induction of CD11b on B cells is a promising marker for selecting an effective mucosal vaccine adjuvant. Abstract : A crucial role for CD11b in germinal-center reactions Graphical Abstract: